Innovators' 'imitation': whether and how does reactive search affect the performance of incumbent firms? Evidence from China. (2nd August 2022) - Guo, Yanting; Deng, Wanru; Hu, Shan; Zheng, Gang
The competitive interaction between incumbents and new entrants has been a central topic in the field of strategic management. This study examines whether and under what conditions reactive search activities help incumbent firms avoid dethronement in the face of external challenges caused by the entry of new entrants. Based on a sample of 236 Chinese firms, we find that both reactive technology search and reactive market search positively affect firm performance. Moreover, the dynamic capability of established firms strengthens the relationship between reactive technology search and innovative performance, as well as that between reactive market search and operational performance. These findings contribute to the literature on competitive dynamics and knowledge search.